Cambios en la estructura y funcionalidad familiar de migrantes venezolanos establecidos en la ciudad de Santa Marta – Colombia, en el primer trimestre del 2022 (2022)
The main objective of this research was to describe the factors that affect the change in the family structure and dynamics of the Venezuelan migrant in Colombian territory, taking into account as main hypothesis that there are factors that can change the family structure and dynamics of the Venezuelan migrant in Colombian territory, which is significantly fulfilled through the results obtained from the application of a mixed design and instruments such as the semi-structured interview and the Family Apgar. It was evidenced that Venezuelan migrant families have changes in their family functionality in a mild way, however, a participant subject, with a score of 9, shows that within his family structure there were changes in the functioning characterized as severe. Therefore, the fulfillment of the hypothesis and the results obtained make evident the influence that socio-cultural factors have on the family structure and dynamics of Venezuelan migrant families.